Popular protest and policing in ascendancy Ireland, 1691-1761 - Watt, Timothy D. (Irish historical monographs series, 2018)
This book explores the connexion between collective action, popular politics and policing in Ireland from the end of the Williamite war in 1691 to the outbreak of the Whiteboy agrarian protest in 1761. It considers the impact made by the people who maintained order - civilian officers, the army and militias, and bands of irregular forces - outlining not only the many problems that they faced but also the effects on Irish society of their abuses. The book highlights the conflict between authorities, who were enforcing laws, and crowds, who were enforcing popular notions of justice, as well as the changes taking place in the ethics of law enforcement. It shows how increasing taxes collected by the Irish government, used mainly to pay for the British army, resulted in a proliferation of violent protests in most parts of Ireland in the early eighteenth century. In addition, the book discusses popular attitudes and belief systems, examines the conduct of rioters and members of the forces of order and reveals the moral compasses used during violent confrontations on both sides of the legal divide. Overall, the book's investigation of large-scale disorder leads us to a better understanding of the relationships between rulers and the ruled in Ireland in this period.